Pengaruh Harga Transfer, Struktur Modal, Dan Kesulitan Keuangan Terhadap Penghindaran Pajak Dengan Ukuran Perusahaan Sebagai Moderasi - Anissa Pujiwaty; Nera Marinda Machdar (Jurnal Riset Akuntansi, 2024)
Taxes are payments to the state that must be paid by individuals or entities for public purposes. Taxes are seen by the state as one of the main sources of income, but are seen by companies as costs that can reduce net profits. Tax avoidance is an action taken by a taxpayer to avoid or reduce the payment of tax that should be owed by using ambiguities or gray areas in tax law to reduce the total tax that must be paid. This research uses quantitative descriptive statistical analysis. The research results show that transfer prices, capital structure, and financial difficulties have a positive impact on tax avoidance practices. However, company size reduces the impact of transfer prices, capital structure, and financial difficulties on tax avoidance practices.